Misfit modernism queer forms of double exile in the twentieth-century novel - González, Octavio R. (Refiguring modernism., 2020)
"Revisits the theme of alienation in modernist literature, finding an alternative aesthetic centered on the experience of double exile. Explores examples drawn from the cultural groupings of the New Negro movement, Parisian expatriates in the 1920s, and the queer expatriate scene in Los Angeles before Stonewall"--